Underdiagnosis of internal anal sphincter trauma following vaginal delivery. (1st February 2023) - O'Leary, B. D.; Kelly, L.; Fitzpatrick, M.; Keane, D. P.
ABSTRACT: Objective: Damage to the anal sphincter during childbirth remains the leading cause of fecal incontinence in women. Defects in the internal (IAS) or external anal sphincter, alongside symptoms and sphincter tone, will generally dictate the suggested mode of delivery in any successive pregnancy. This study aimed to examine using endoanal ultrasonography the prevalence of IAS damage in women referred with Grade‐3a or ‐3b obstetric anal sphincter injury (OASI) in a tertiary‐referral perineal clinic. Methods: This was a retrospective observational study of all women referred to a tertiary‐referral perineal clinic after primary repair of OASI (Grade 3a–c, 4) diagnosed for the first time following vaginal delivery between January 2016 and December 2019, inclusive. Women were assessed using the Wexner bowel continence questionnaire, digital examination of sphincter tone and endoanal ultrasound. Injuries in each sphincter were classified as a scar (≤ 30°) or defect (> 30–90° or > 90°) on endoanal imaging in the axial plane. Results: In total, 615 women were referred following primary repair of OASI. Sonographic evidence of damage to the IAS was seen in 9.1% (46/506) of women diagnosed with a Grade‐3a/3b injury. In women referred with a Grade‐3a/3b tear, symptom scores were statistically higher ( P  = 0.025) in those with an IAS defect > 30° compared to those with an intact or scarred IAS, although the median score was zero in both groups. The proportion of women in each group with severe symptoms (score > 9) was similar (2.6% vs 6.5%; P  = 0.148). Among women referred with a Grade‐3a/3b tear, sphincter tone was reduced more frequently in those with a defect of the IAS than in those with an intact or scarred IAS (52.2% vs 11.7%; odds ratio, 8.14 (95% CI, 4.26–15.67); P  < 0.001). Regardless of the reason for referral, women with reduced sphincter tone on rectal examination were four times as likely to have had an IAS defect > 30° than were those with normal resting tone (risk ratio, 4.58 (95% CI, 3.25–6.45); P  < 0.001). Conclusions: One in 11 women diagnosed with a Grade‐3a or ‐3b tear have evidence of damage to their IAS on endoanal ultrasound. Damage to this muscle is linked to fecal incontinence in women and can have a significant impact on the planning of any future deliveries. This study highlights the importance of established perineal clinics with access to ultrasound. Nonetheless, if reduced sphincter tone is felt on rectal examination, a clinician should have a high index of suspicion for an occult IAS injury. © 2022 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.